Advances in Effects of Sound Waves on Plants - Reda HE Hassanien; Tian-zhen HOU; Yu-feng LI; Bao-ming LI (Journal of Integrative Agriculture, 2014)
Sound waves technology has been applied to different plants. It has been found that sound waves were at different frequencies, sound pressure levels (SPLs), exposure periods, and distances from the source of sound influence plant growth. Experiments have been conducted in the open field and under greenhouse growing conditions with different levels of audible sound frequencies and sound pressure levels. Sound waves at 1 kHz and 100 dB for 1 h within a distance of 0.20 m could significantly promote the division and cell wall fluidity of callus cells and also significantly enhance the activity of protective enzymes and endogenous hormones. Sound waves stimulation could increase the plant plasma-membrane H+-ATPase activity, the contents of soluble sugar, soluble protein, and amylase activity of callus. Moreover, sound waves could increase the content of RNA and the level of transcription. Stress-induced genes could switch on under sound stimulation. Sound waves at 0.1–1 kHz and SPL of (70±5) dB for 3 h from plant acoustic frequency technology (PAFT) generator within a distance ranged from 30 to 60 m every other day significantly increased the yield of sweet pepper, cucumber and tomato by 30.05, 37.1 and 13.2%, respectively. Furthermore, the yield of lettuce, spinach, cotton, rice, and wheat were increased by 19.6, 22.7, 11.4, 5.7, and 17.0%, respectively. Sound waves may also strengthen plant immune systems. It has been proved that spider mite, aphids, gray mold, late blight and virus disease of tomatoes in the greenhouses decreased by 6.0, 8.0, 9.0, 11.0, and 8.0%, respectively, and the sheath blight of rice was reduced by 50%. This paper provides an overview of literature for the effects of sound waves on various growth parameters of plant at different growth stages.